2010
DOI: 10.1148/radiol.10091701
|View full text |Cite
|
Sign up to set email alerts
|

Resting Brain Connectivity: Changes during the Progress of Alzheimer Disease

Abstract: Changes in PCC functional connectivity comprised bidirectional alterations in the resting networks in AD-affected brains, and the impaired resting functional connectivity seemed to change with AD progression. Therefore, alterations in functional connectivity in the default mode network might play a role in the progression of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
200
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(229 citation statements)
references
References 33 publications
26
200
0
3
Order By: Relevance
“…48 Similarly, increased resting-state connectivity between the PCC and other DMN regions has been noted in elderly individuals with elevated regional brain atrophy and memory complaints, 91 in MCI, 47,92,93 and in the very early stages of AD. 85,94,95 The concordance between the current results and those in neurodegenerative disease orients us to the potential consequences of TBIinduced network changes on long-term neurological status. Wholebrain functional connectivity analyses, naïve of any seed definitions, have suggested that individuals advance toward a more ''healthy'' state in the months after injury, 13 corresponding to significant clinical recovery in the first year.…”
Section: Potential Markers Of Long-term Outcomesupporting
confidence: 69%
See 1 more Smart Citation
“…48 Similarly, increased resting-state connectivity between the PCC and other DMN regions has been noted in elderly individuals with elevated regional brain atrophy and memory complaints, 91 in MCI, 47,92,93 and in the very early stages of AD. 85,94,95 The concordance between the current results and those in neurodegenerative disease orients us to the potential consequences of TBIinduced network changes on long-term neurological status. Wholebrain functional connectivity analyses, naïve of any seed definitions, have suggested that individuals advance toward a more ''healthy'' state in the months after injury, 13 corresponding to significant clinical recovery in the first year.…”
Section: Potential Markers Of Long-term Outcomesupporting
confidence: 69%
“…For example, it has been found that restingstate antiphase synchrony between regions of different networks is impaired in AD, 48,[83][84][85] and the loss of antiphase synchrony between posterior regions and frontal cortex in AD-risk populations may be especially relevant to the development of AD. 47 Hippocampal hypersynchrony with proximal regions and/or other regions of the DMN has been noted in risk groups for AD, including individuals positive for the apolipoprotein Ee4 allele [86][87][88] and mild cognitive impairment (MCI) patients 89,90 as well as individuals with early AD itself.…”
Section: Potential Markers Of Long-term Outcomementioning
confidence: 99%
“…Analyses of AD‐related functional brain network differences associated with the DMN but not part of the DMN report changes in superior parietal and occipital regions (Agosta et al., 2012; Lee et al., 2016). These findings are consistent with those in resting and visual fMRI studies that report affected visual functioning accompanied by differences in the visual cortices (Alegret et al., 2010; Lehmann et al., 2013; Wang et al., 2015; Zhang et al., 2010) and the idea that deviations from the typical pathology, such as the involvement of functionally specific brain regions, drive the variation in neurodegenerative variation in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The DMN is typically found deactivated during cognitive tasks requiring externally focused attention and activated during internally focused mental tasks, such as episodic memory retrieval, mental state attribution, and visual imagery (Buckner, Andrews-Hanna, & Schacter, 2008;Mason et al, 2007;Raichle et al, 2001;Shulman et al, 1997). In addition to the regional atrophy and neuronal hypometabolism affecting DMN nodes, disruptions in functional connectivity of the DMN in AD dementia have been widely replicated (Agosta et al, 2012;Binnewijzend et al, 2012;Greicius, Srivastava, Reiss, & Menon, 2004), and have been linked to core memory and visuospatial deficits Supekar, Menon, Rubin, Musen, & Greicius, 2008;Zhang et al, 2010). Intriguingly, connectivity disruption and impaired task-related down regulation of the DMN may already emerge during the presymptomatic phase of AD as modeled cross-sectionally on the basis of imaging evidence of cortical amyloid pathology Sperling et al, 2009) or an apolipoprotein E4 (APOE4) positive genotype, which is a major genetic risk factor for late onset AD (Damoiseaux et al, 2012;Machulda et al, 2011;Persson et al, 2008).…”
Section: Functional Connectivity Changes In the Course Of Admentioning
confidence: 99%